Research in Systems Analysis and Design: Models and Methods 4th SIGSAND/PLAIS EuroSymposium 2011, Gdask, Poland, September 29, 2011, Revised Selected Papers - Wrycza, Stanisław (Lecture Notes in Business Information Processing,1865-1348 ; 9340, 2011)
This book constitutes the proceedings of the 4th EuroSymposium on Systems Analysis and Design, SIGSAND/PLAIS 2011, held in Gdask, Poland, in September 2011. The objective of this symposium is to promote and develop high-quality research on all issues related to systems analysis and design (SAND). It provides a forum for SAND researchers and practitioners in Europe and beyond to interact, collaborate, and develop their field. The 9 papers were carefully reviewed and selected from 20 submissions. An additional revision took place after the conference to incorporate discussion results from the presentation. The contributions are organized into topical sections on business process modeling, integrated systems development, and software development.